The performance of preferential procurement at the SABC - Kaseke, Trevor Farayi (My University, 2017)
This study primarily sought to establish how a state owned entity, as an expected enthusiastic proponent of the State’s black economic empowerment efforts, had performed in terms of preferential procurement from majority black-owned vendors. It also sought to find out to what extent, if any, the fortunes of majority black-owned vendors had extended beyond the typical categories of catering services, cleaning services and security services. The study employed a mixed-methods approach, combining quantitative and qualitative analysis. The basis of the quantitative analysis was procurementrelated documents, while the basis of the qualitative analysis was interviews conducted with personnel selected either for their involvement in the supply chain management process, or were the users of services or products procured by the South African Broadcasting Corporation (SABC) SOC Ltd. Descriptive statistics were used to analyse the data. While the full population of transactions and vendors used during the period of analysis (2010 – 2015) was available, gaps in required information, as well as some withheld information, presented a limitation in terms of the data that could be used to answer the research questions. As a result of this limitation, the results of this study are indicative and not definitive. In terms of the primary research question the study found the bulk of procurement having been placed through vendors within B-BBEE levels 1 to 4. There were also significant increases in the proportion of procurement spend going to EMEs and QSEs over the analysis period. In terms of making use of majority black-owned vendors, there was a marked increase over the analysis period, with marked increases in the use of majority black-owned EMEs and QSEs. In terms of the sub-question, the study found a high proportion of spend, or increasing proportions of spend, that went to vendors offering services and products within the SABC’s core business areas such as Content Production. The qualitative interviews conducted revealed that this performance by the SABC has largely been ‘accidental’. The SABC has no strategy for black economic empowerment in general, and for preferential procurement or enterprise development in particular. All that the SABC appears to have done is implement a supply chain management policy that is aligned with the government’s black economic empowerment legislation and regulations. This particular finding appears to demonstrate how the State’s policies and related pieces of regulation are intended to work. At the barest minimum, just implementing internal policies aligned to the legislation and regulations should go some way in achieving the national imperative of broadbased black economic empowerment. The report concludes with recommendations on how the analysis from this study could be built on, as well as steps the SABC could take to improve its performance in terms of preferential procurement and enterprise development.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50% fulfilment of the requirement for the degree of Master of Management (in the field of Monitoring and Evaluation), December 2017
Keywords: South African Broadcasting Corporation; Affirmative action programs--South Africa; Government purchasing--South Africa